Cyber Espionage of F-15 Fighter Jet Data Impact To U.S. – China Relations - Triwahyuni, D; Azhar, M; Cahya, D; Andika, R (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to examine the impact of cyber espionage activities related to the F-35 Joint Strike Fighter Military Project on the relationship between the United States and China. Allegations of Chinese espionage activities first surfaced in the public sphere in early 2015. German media Der Spiegel published a number of pieces of information confirming the result of a data breach by subcontractor Lockheed Martin that allowed China access to classified data on the F35. Cyber espionage is often carried out in order to achieve the national interests of a country in the military, political and economic fields. China's practice of cyber espionage against the United States is also an effort to fulfill its national interests. This study used qualitative methods with data collection techniques through literature study, review of books, journals, newspapers, internet media, and as well as other references. After the data that has been collected is classified according to the problems that have been identified, then it is continued by carrying out systematic content analysis and comparison with information, so that it can answer the problems raised. The results of the study show that the United States and China have not issued significant policies or cooperation in maintaining their cyber security, because they do not want bilateral relations in the economic field to be disrupted due to the data hacking incident. They only agreed that they would not carry out data hacking sponsored or assisted by their respective governments. They are reluctant to issue policies that punish one of them because they want to maintain bilateral relations for a long time, especially in the economic field.